2020
DOI: 10.1097/md.0000000000018611
|View full text |Cite|
|
Sign up to set email alerts
|

Effective/cost effective interventions of child mental health problems in low- and middle-income countries (LAMIC)

Abstract: Background: This systematic review protocol aims to examine the evidence of effectiveness and cost-effectiveness of interventions for children and adolescents with, or at risk of developing mental disorders in low- and middle-income countries (LAMICs). Methods: We will search Medline Ovid, EMBASE Ovid, PsycINFO Ovid, CINAHL, LILACS, BDENF and IBECS. We will include randomised and non-randomised controlled trials, economic modelling studies and economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The study design and report of this review is based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) [14]. The protocol of this review is registered in PROSPERO under the number CRD42019129376 and has been previously published [15].…”
Section: Methodsmentioning
confidence: 99%
“…The study design and report of this review is based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) [14]. The protocol of this review is registered in PROSPERO under the number CRD42019129376 and has been previously published [15].…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for this systematic review was previously published in Medicine (Baltimore) (18) and is registered in…”
Section: Protocol and Registrationmentioning
confidence: 99%
“…Details on our search strategy and other relevant methodological aspects of our review can be found in our study protocol, which has been previously published (18).…”
Section: Searchmentioning
confidence: 99%
“…Approximately one-third of the studies were excluded because they were either study protocols, duplicates, abstracts, editorial letters, or were not CEAs (i.e., the study did not consider both cost and clinical outcomes). [31][32][33][34][35][36][37][38][39][40] Of the remaining studies, the most common reasons for exclusion were that either the modelled population or the intervention was not aligned with the research question (n = 22). With regard to the population, there were 2 common reasons for exclusion: either the mean age was outside the age range of interest (n = 4) or the study did not specifically consider a population with an eating disorder (n = 4) (e.g., the study populations included mental health indications other than eating disorders or the population only had to have self-reported body image concerns).…”
Section: Quantity Of Research Availablementioning
confidence: 99%